Molecular design of star-shaped benzotrithiophene materials for organic electronics. Issue 36 (5th September 2019) - Santi, Saverio; Rossi, Serena
Graphical abstract: Highlights: High performance of BTT-based photovoltaic devices and field-effect transistors. The 3D-functionalization increases the electronic performance of the materials. Intrinsic charge-carrier mobility in bulk samples along columnar stacking. High-areal capacitors for high-life cycle capacitive electrode applications. Implementation on perovskite approaches the performance of silicon solar cells. Abstract: Progresses in the design and application of conjugated small molecules, oligomers and polymers have empowered rapid development of organic electronic technology as an alternative to conventional devices. Among the numerous organic electronic materials, benzotrithiophene (BTT)-based oligomers and polymers have recently come in the limelight demonstrating great potential in organic electronics as high performance photovoltaic devices, field-effect transistors, electrochromic materials, high-area capacitors and charge carrier discotic liquid crystals. In this digest, we propose an overview of the organic electronic materials based on BTT isomers, highlighting the structure-performance relationship. The results obtained so far clearly indicate that the BTT isomers are among the most promising building blocks for the development π-extended materials for optoelectronic applications in the near future.